Male participation and sharing of responsibility in strengthening family planning activities in Malaysia. - Abd Manaf , Rosliza; Mohamed, Majdah (Malaysian Public Health Specialist Association, 2010)
Family plannin g is one of the main pillars of safe motherhood initiatives. It is therefore a very crucial area that needs continuous strengthening and improvement in order to reduce maternal morbidity and mortality which will ultimately improve the general condition of women. Findings from the Confidential Enquiries into Maternal Death (CEMD) Malaysia Report 2001 – 2005 revealed that up to 70% of the maternal deaths never practiced any form of family planning. The contraceptive prevalence rate (CPR) in Malaysia for the y ear 2004 was 51.7% compared to Thailand, Vietnam and Singapore which was 79%, 74% and 74% respectively. One neglected area that has never been emphasized seriously in the family planning programme in Malaysia is male participation, gender awareness and sha ring of responsibility by both partners. In realizing this, efforts have been made to include men as target groups in the national family planning programme. This paper will highlight the importance of optimum gender relations and sharing of responsibility with special emphasis towards the role of husbands and male medical personnel in the effort to improve family planning activities. It will also discuss the efforts put by the Ministry of Health in order to create gender awareness and encourage male participation in family planning.